Characterization of Phosphatidylserine-dependent β2-Glycoprotein I Macrophage Interactions - Krishnakumar Balasubramanian; Alan J. Schroit (1998)
The binding and uptake of phosphatidylserine (PS)-expressing cells appears to involve multiple receptor-mediated systems that recognize the lipid either directly or indirectly through intermediate proteins that form a molecular bridge between the cells. Here we show that β2-glycoprotein I (β2GPI), a 50-kDa serum glycoprotein, binds PS-containing vesicles and serves as an intermediate for the interaction of these vesicles with macrophages. Chemical modification of lysines and cysteines abolished β2GPI-dependent PS uptake by inhibiting the binding of PS to β2GPI and the binding of PS·β2GPI complex to macrophages, respectively. Recognition was mediated by β2GPI and not by the lipid because antibodies to β2GPI inhibited binding of the complex to macrophages. These results indicate that human (THP-1-derived) macrophages bind β2GPI only after it is bound to its lipid ligand. Competition experiments with monosaccharides that inhibit lectin-dependent interactions, and PS·β2GPI binding experiments using deglycosylated β2GPI, suggested that carbohydrate residues were not required for macrophage recognition of the complex. Antibodies to putative macrophage PS receptors (CD36, CD68, and CD14) did not inhibit uptake of the complex. These data suggest that β2GPI can bind cells that fail to maintain membrane lipid asymmetry and generate a specific bridging moiety that is recognized for clearance by a phagocyte receptor that is distinct from CD36, CD68, and CD14. The binding and uptake of phosphatidylserine (PS)-expressing cells appears to involve multiple receptor-mediated systems that recognize the lipid either directly or indirectly through intermediate proteins that form a molecular bridge between the cells. Here we show that β2-glycoprotein I (β2GPI), a 50-kDa serum glycoprotein, binds PS-containing vesicles and serves as an intermediate for the interaction of these vesicles with macrophages. Chemical modification of lysines and cysteines abolished β2GPI-dependent PS uptake by inhibiting the binding of PS to β2GPI and the binding of PS·β2GPI complex to macrophages, respectively. Recognition was mediated by β2GPI and not by the lipid because antibodies to β2GPI inhibited binding of the complex to macrophages. These results indicate that human (THP-1-derived) macrophages bind β2GPI only after it is bound to its lipid ligand. Competition experiments with monosaccharides that inhibit lectin-dependent interactions, and PS·β2GPI binding experiments using deglycosylated β2GPI, suggested that carbohydrate residues were not required for macrophage recognition of the complex. Antibodies to putative macrophage PS receptors (CD36, CD68, and CD14) did not inhibit uptake of the complex. These data suggest that β2GPI can bind cells that fail to maintain membrane lipid asymmetry and generate a specific bridging moiety that is recognized for clearance by a phagocyte receptor that is distinct from CD36, CD68, and CD14. β2-glycoprotein I phosphatidylcholine phosphatidylserine β2GPI complexed to vesicles composed of PS/PC (1/1) Tris-buffered saline N-ethylmaleimide. The emergence of phosphatidylserine (PS)1 in the cells outer leaflet results in the expression of altered cell surface properties that regulates their recognition by phagocytes (1Fadok V.A. Voelker D.R. Campbell P.A. Cohen J.J. Bratton D.L. Henson P.M. J. Immunol. 1992; 148: 2207-2216Crossref PubMed Google Scholar, 2Pradhan D. Krahling S. Williamson P. Schlegel R.A. Mol. Biol. Cell. 1997; 8: 767-778Crossref PubMed Scopus (127) Google Scholar, 3Zwaal R.F.A. Schroit A.J. Blood. 1997; 89: 1121-1132Crossref PubMed Google Scholar). Although PS recognition might include binding to specific PS receptors (1Fadok V.A. Voelker D.R. Campbell P.A. Cohen J.J. Bratton D.L. Henson P.M. J. Immunol. 1992; 148: 2207-2216Crossref PubMed Google Scholar, 4Ramprasad M.P. Fischer W. Witztum J.L. Sambrano G.R. Quehenberger O. Steinberg D. Proc. Natl. Acad. Sci. U. S. A. 1995; 92: 9580-9584Crossref PubMed Scopus (299) Google Scholar, 5Sambrano G.R. Steinberg D. Proc. Natl. Acad. Sci. U. S. A. 1995; 92: 1396-1400Crossref PubMed Scopus (278) Google Scholar), class B scavenger receptors (6Rigotti A. Acton S.L Krieger M. J. Biol. Chem. 1995; 270: 16221-16224Abstract Full Text Full Text PDF PubMed Scopus (498) Google Scholar, 7Ren Y. Silverstein R.L. Allen J. Savill J. J. Exp. Med. 1995; 181: 1857-1862Crossref PubMed Scopus (354) Google Scholar, 8Fukasawa M. Adachi H. Hirota K. Tsujimoto M. Arai H. Inoue K. Exp. Cell. Res. 1996; 222: 246-250Crossref PubMed Scopus (139) Google Scholar), the lipopolysaccharide receptor (2Pradhan D. Krahling S. Williamson P. Schlegel R.A. Mol. Biol. Cell. 1997; 8: 767-778Crossref PubMed Scopus (127) Google Scholar,9Flora P.K. Gregory C.D. Eur. J. Immunol. 1994; 24: 2625-2632Crossref PubMed Scopus (116) Google Scholar, 10Yu B. Hailman E. Wright S.D. J. Clin. Invest. 1997; 99: 315-324Crossref PubMed Scopus (200) Google Scholar, 11Devitt A. Moffat O.D. Raykundalia C. Capra J.D. Simons D.L. Gregory C.D. Nature. 1998; 392: 505-509Crossref PubMed Scopus (575) Google Scholar) or thrombospondin-dependent vitronectin receptors (12Savill J. Fadok V. Henson P. Haslett C. Immunol. Today. 1993; 14: 131-136Abstract Full Text PDF PubMed Scopus (989) Google Scholar), recent evidence suggests that β2GPI, a relatively abundant plasma protein (13Cohnen G. J. Lab. Clin. Med. 1969; 75: 212-216Google Scholar), binds PS (14Schousboe I. Biochim. Biophys. Acta. 1979; 579: 396-408Crossref PubMed Scopus (45) Google Scholar, 15Wurm H.J. Int. J. Biochem. 1984; 16: 511-515Crossref PubMed Scopus (225) Google Scholar) and mediates its uptake by phagocytic cells. Indeed, the binding of β2GPI to PS-containing liposomes (16Chonn A. Semple S.C. Cullis P.R. J. Biol. Chem. 1995; 270: 25845-25849Abstract Full Text Full Text PDF PubMed Scopus (176) Google Scholar), PS expressing apoptotic thymocytes (17Price B.E. Rauch J. Shia M.A. Walsh M.T. Lieberthal W. Gilligan H.M. O'Laughlin T. Koh J.S. Levine J.S. J. Immunol. 1996; 157: 2201-2208PubMed Google Scholar,18Balasubramanian K. Chandra J. Schroit A.J. J. Biol. Chem. 1997; 272: 31113-31117Abstract Full Text Full Text PDF PubMed Scopus (146) Google Scholar) and symmetric red blood cell ghosts (18Balasubramanian K. Chandra J. Schroit A.J. J. Biol. Chem. 1997; 272: 31113-31117Abstract Full Text Full Text PDF PubMed Scopus (146) Google Scholar) has been shown to influence their clearance and phagocytosis. These observations raise the possibility that, in addition to regulating thrombosis (19Brighton T.A. Hogg P.J. Dai Y.-P. Murray B.H. Choing B.H. Chesterman C.N. Br. J. Hematol. 1996; 93: 185-194Crossref PubMed Scopus (89) Google Scholar), β2GPI plays an important physiologic role by mediating the recognition of cells that fail to preserve membrane lipid asymmetry. Although the binding of β2GPI to PS-containing surfaces has been well characterized (15Wurm H.J. Int. J. Biochem. 1984; 16: 511-515Crossref PubMed Scopus (225) Google Scholar, 20Willems G.M. Janssen M.P. Pelsers M.A.L. Comfurius P. Galli M. Zwaal R.F.A. Bevers E.M. Biochemistry. 1996; 35: 13833-13842Crossref PubMed Scopus (197) Google Scholar, 21Hagihara Y. Goto Y. Kato H. Yoshimura T. J. Biochem. (Tokyo). 1995; 118: 129-136Crossref PubMed Scopus (45) Google Scholar), little is known about its interaction with phagocytes. Here we report on the nature of β2GPI/phagocyte interactions using human THP-1-derived macrophages as a model system. We show that human β2GPI binds macrophages only after it is complexed to its lipid ligand. Our results suggest that PS binding by β2GPI induces a lipid-dependent conformational change that exposes a specific epitope that is recognized by a macrophage receptor that is distinct from other previously described lipid receptors. Phospholipids were purchased from Avanti Polar Lipids (Alabaster, AL). Carrier-freeN-[3-(3-[125I]iodo-4-hydroxybenzyl)propionyl]dipalmitoylphosphatidylethanolamine (125I-PE) was synthesized as described previously (22Schroit A.J. Madsen J. Biochemistry. 1983; 22: 3617-3623Crossref PubMed Scopus (17) Google Scholar). RPMI 1640, fetal calf serum, and penicillin/streptomycin were from Life Technologies, Inc. Phorbol 12-myristate 13-acetate and the β2GPI chemical modification reagents were from Sigma. Neuraminidase (Clostridium perfringens),N-glycosidase-F (recombinant, Escherichia coli) and O-glycosidase-F (Diplococcus pneumoniae) were from Boehringer Mannheim. β2GPI was purified from pooled human plasma (Gulf Coast Regional Blood Center, Houston, TX) by perchloric acid precipitation, ion exchange chromatograhy, and heparin affinity chromatography as described previously (15Wurm H.J. Int. J. Biochem. 1984; 16: 511-515Crossref PubMed Scopus (225) Google Scholar, 23Poltz E. Kostner G.M. FEBS Lett. 1979; 102: 183-186Crossref PubMed Scopus (197) Google Scholar). Antibodies to β2GPI were produced in rabbits and IgG was purified over protein A-Sepharose. F(ab′)2 was produced from purified IgG by pepsin digestion followed by gel filtration and protein A-Sepharose chromatography to remove undigested IgG. Monoclonal antibodies against CD11b (clone 44), CD36 (clone SM0), and CD14 (UCHM-1) were from Sigma. Antibodies to CD14 (clone TUK4) and CD68 (clone KP1) were purchased from Dako. CD14 antibodies (clone 61D3), kindly provided by J. D. Capra (Oklahoma Medical Research Foundation), were purified from ascitis on protein G-Sepharose. Multilamellar vesicles and small lipid vesicles containing 125I-PE (1 μCi/ml) were prepared from the indicated lipids (1 mg/ml) by vortexing and sonication, respectively. ForN-ethylmaleimide (NEM), 30 nmol of β2GPI in TBS (20 mm Tris, 150 mM NaCl, pH 7.4) were treated with 4.8 μmol of NEM (80 mm stock in TBS) for 60 min at 20 °C. For diketene, 30 nmol of β2GPI in borate buffer (300 mm, pH 9.5) were treated with 2 μmol of diketene for 20 min at 20 °C (24Mehdi H. Yang X. Peeples M.E. Virology. 1996; 217: 58-66Crossref PubMed Scopus (30) Google Scholar). For phenacylbromide, 30 nmol of β2GPI in TBS were treated with 7.0 μmol of phenacylbromide (238 mm stock in Me2SO) for 60 min at 37 °C (25Connor J. Pak C.H. Zwaal R.F.A. Schroit A.J. J. Biol. Chem. 1992; 267: 19412-19417Abstract Full Text PDF PubMed Google Scholar). For phenylglyoxal, 30 nmol of β2GPI in carbonate/bicarbonate buffer (125 mm, pH 7.5) were labeled with 22 μmol of phenylglyoxal (745 mm stock in Me2SO) for 90 min at 20 °C (26Daemen F.J.M. Riordan J.F. Biochemistry. 1974; 13: 2865-2871Crossref PubMed Scopus (68) Google Scholar). For cyclohexanedione, 30 nmol of β2GPI in borate buffer (0.1 m, pH 8.0) were labeled with 10 μmol of 1,2-cyclohexanedione (24Mehdi H. Yang X. Peeples M.E. Virology. 1996; 217: 58-66Crossref PubMed Scopus (30) Google Scholar). Excess reagents were removed by gel filtration or dialysis. β2GPI was desialyated by treating 20 nmol of β2GPI in phosphate buffer (100 mm, pH 6.0) with neuraminidase (2 units) for 24 h at 37 °C according to the manufacturer's instructions. The product was purified by ion-exchange chromatography on DEAE-Sephacel equilibrated with 50 mm Tris, 20 mm NaCl, pH 7.2. The eluate was pooled and concentrated by heparin-Sepharose affinity chromatography as described previously (15Wurm H.J. Int. J. Biochem. 1984; 16: 511-515Crossref PubMed Scopus (225) Google Scholar,23Poltz E. Kostner G.M. FEBS Lett. 1979; 102: 183-186Crossref PubMed Scopus (197) Google Scholar). Complete deglycosylation of β2GPI was achieved by incubating 30 nmol of β2GPI in phosphate buffer (100 mm, pH 7.2) with neuraminidase (1 unit),N-glycosidase-F (10 units), and O-glycosidase-F (25 milliunits) for 48 h at 37 °C as described by the manufacturer. The sample was purified on DEAE-Sephacel/heparin affinity chromatography as described above. The binding of β2GPI to phospholipids was monitored by lipoblotting and by gel diffusion using 125I-labeled small unilamellar vesicle. For the lipoblot, unmodified and chemically modified β2GPI were electrophoresed on 10% SDS-polyacrylamide gels and transferred to polyvinylidene difluoride membrane. The membrane was blocked with 1% ovalbumin in TBS and incubated for 60 min at 20 °C with 125I-labeled PS/PC (1/1) small unilamellar vesicles at 0.5 mg of lipid/ml in TBS. Unbound lipid was removed by washing in TBS. Binding of the labeled vesicles to β2GPI was determined by autoradiography. For the gel diffusion, microscope slides were coated with 0.9% agarose in 10 mmTris-HCl, pH 7.4 with or without the indicated inhibitors. Two holes (20-μl loading volume) were punched 1 cm apart and filled with β2GPI (300 μg/ml) and 125I-labeled PS/PC (1/1) small unilamellar vesicles. The plates were developed for 24 h, and unbound protein and lipid was removed by washing for 24 h in the same buffer. The gels were then dried, and precipitates were detected by autoradiography (18Balasubramanian K. Chandra J. Schroit A.J. J. Biol. Chem. 1997; 272: 31113-31117Abstract Full Text Full Text PDF PubMed Scopus (146) Google Scholar). Human THP-1 monocytic leukemia cells were grown in RPMI 1640 containing 10% fetal calf serum, 100 units/ml penicillin/streptomycin, and 2 mml-glutamine. Cells were maintained in a humidified atmosphere of 5% CO2at 37 °C. The cells were differentiated to macrophages with phorbol 12-myristate 13-acetate (0.1 nmol/2.5 × 106 cells) for 72 h. Differentiation was verified by staining with CD11b antibodies (27Schwende H. Fitzke E. Ambs P. Dieter P. J. Leuk. Biol. 1996; 59: 555-561Crossref PubMed Scopus (457) Google Scholar). Adherent macrophages (∼106cells) in 24-well Costar plates were washed with TBS and resuspended in 250 μl of RPMI 1640 medium (without serum) containing multilamellar vesicle-β2GPI complexes (200 μg of lipid/100 μg of β2GPI/ml). The cells were incubated at 37 °C for the indicated time, washed, and solubilized in 0.2% SDS. Lipid uptake was determined by scintillation counting. The effect of β2GPI and PS on the uptake of 125I-labeled PS-containing vesicles was determined. Fig. 1 A shows the uptake of PS/PC (1/1) vesicles by macrophages as a function of β2GPI concentration. Maximal uptake occurred at ∼2 μm β2GPI, which is approximately half the concentration found in normal human serum (13Cohnen G. J. Lab. Clin. Med. 1969; 75: 212-216Google Scholar). Fig. 1 Bshows the effect of PS concentration on vesicle uptake. The inclusion of β2GPI enhanced the uptake of 50 mol % PS >4-fold during the 1-h time course of the experiment. Interestingly, the degree of β2GPI-dependent enhancement of uptake diminished at PS concentration >70 mol %, suggesting the existence of both β2GPI-dependent and -independent uptake mechanisms. Increasing the incubation time resulted in ∼7-fold enhancement in β2GPI-dependent uptake (Fig. 1 C). The influence of β2GPI on the uptake of PS vesicles by macrophages can be explained by at least two mechanisms. 1) β2GPI binds independent of its lipid ligand (PS) to macrophages, and 2) the binding of β2GPI to macrophages is dependent on its prior binding to PS. To differentiate between these two possibilities, macrophages were preincubated with β2GPI, washed, and then assessed for lipid uptake. Fig. 2 A shows that macrophages incubated with β2GPI in this manner did not exhibit enhanced PS uptake. On the other hand, uptake was similar to control levels when PS vesicles were added to macrophages that were not washed free of β2GPI, suggesting that β2GPI binding to macrophages has a lipid dependence. To verify that binding of β2GPI was ligand-dependent, macrophages were incubated for 20 min with β2GPI alone, or in complex with PS, and assessed for cell-bound β2GPI by staining with fluorescent β2GPI antibodies. No fluorescence was seen on cells incubated with β2GPI alone confirming that β2GPI binding is ligand dependent (Fig. 2 A, inset). Indeed, acylation of lysines critical to β2GPI lipid binding (28Hunt J. Krilis S. J. Immunol. 1994; 152: 653-659PubMed Google Scholar) with diketene abrogated the uptake of PS vesicles (Fig. 2 B). While β2GPI is clearly required for the efficient uptake of PS, it is possible that the binding of the PS·β2GPI complex to the macrophage membrane triggers a generalized phagocytic pathway that engulfs particles independent of β2GPI. To test this, mixed PS/PC and PC vesicle experiments in which the125I-label was incorporated into either population was carried out. Fig. 3 shows that cells bound 125I-PS/PC vesicles but not to 125I-PC vesicles. Moreover, when mixed PS/PC and PC vesicles in which the radiolabel was incorporated in the PC population was added to the macrophages, uptake of the radiolabel was similar to that of125I-PC vesicles alone, indicating selective uptake of the β2GPI bound population only. To assess the amino acid moieties critical to macrophage binding of PS·β2GPI complexes, β2GPI was treated with the indicated reagents, purified, complexed to 125I-PS/PC vesicles, and assessed for macrophage uptake. As shown in Fig. 4 A, modification of histidines (phenacylbromide) and arginines (cyclohexanedione and phenylglyoxal) did not inhibit uptake, 2The reason for the ∼7-fold increase in PS·β2GPI uptake in the case of phenylglyoxal-modified β2GPI is not known.whereas blocking of lysines (diketene) and cysteines (NEM) did. Although inhibition in the case of lysine modification was indirect (due to inhibition in ligand binding; see Fig. 2 B), acylation of cysteines with NEM directly inhibited the binding of PS·β2GPI to macrophages. This was concluded from the results of lipoblot (Fig. 4 C) and gel diffusion (Fig. 4 D) experiments which showed that the NEM-treated protein, unlike diketene-treated protein, still bound 125I-PS/PC vesicles, and by the finding that the inhibition was bypassed by the addition of β2GPI antibodies (Fig. 4 B). It should be noted that circumvention of inhibition by β2GPI antibodies was due to the binding of the PS·β2GPI·IgG complex to the Fc receptor of the cells. Similar experiments carried out with F(ab′)2 fragments resulted in inhibition of PS·β2GPI uptake, suggesting that the antibodies bind to a β2GPI site that is critical to macrophage recognition (Fig. 5).Figure 5Effect of β2GPI F(ab′)2 on PS·β2GPI uptake. A,125I-PC and 125I-PS/PC vesicles were preincubated with and without β2GPI. Macrophage uptake was then determined in the presence of the indicated antibody at 200 μg/ml. B, the upper and lower curves show vesicles incubated with the indicated concentrations of β2GPI IgG and β2GPI F(ab′)2, respectively. (•), 125I-PS·β2GPI complex; (■) 125I-PC/PS vesicles alone.View Large Image Figure ViewerDownload Hi-res image Download (PPT) To determine the role carbohydrates might play in the binding of PS·β2GPI to macrophages, PS·β2GPI was incubated with macrophages in the presence of various monosaccharides. The data presented in Fig. 6 Ashow that these monosaccharrides did not inhibit uptake, suggesting that macrophage PS·β2GPI interactions do not involve lectin-like carbohydrate binding moieties. Interestingly, deglycosylation of β2GPI enhanced uptake ∼3-fold (Fig. 6 B), possibly due to decreased charge repulsion by removal of sialic acid residues. To determine the nature of PS·β2GPI-macrophage interactions, uptake was assessed in the presence of amino acids and negatively charged groups. Table I shows that lysine and arginine inhibited uptake, whereas serine, leucine, and valine did not. Interestingly, while phosphoserine, phosphate, succinate, and butyrate inhibited uptake, aspartate and glutamate were without effect. Analysis of PS·β2GPI interaction by gel diffusion (18Balasubramanian K. Chandra J. Schroit A.J. J. Biol. Chem. 1997; 272: 31113-31117Abstract Full Text Full Text PDF PubMed Scopus (146) Google Scholar) in the presence of the inhibitors (data not shown) indicated that inhibition of binding to the macrophage surface was not because of dissociation of the PS·β2GPI complex. It should be noted that these inhibitors were specific for PS·β2GPI complexes because they did not significantly influence macrophage uptake of PS alone (Table I).Table IEffect of charge on PS/β2GPI uptake by macrophagesUptake1-aResults are expressed as percent uptake of control PS·β2GPI and PS alone.PS/β2GPIPS alone%Control100.0100.0Lys31.984.0Arg46.875.9Asp80.475.5His76.0125.0Glu107.0110.0Gln82.6106.6Ser99.588.8Leu98.394.8Val114.5103.0Phosphoserine40.988.3Phosphate54.679.2Succinate30.787.5Butyrate52.279.4125I-Labeled PS/PC (1/1) vesicles were preincubated with β2GPI at 20 °C. After 1 h macrophage uptake was determined in the presence of the indicated inhibitors (20 mm).1-a Results are expressed as percent uptake of control PS·β2GPI and PS alone. Open table in a new tab 125I-Labeled PS/PC (1/1) vesicles were preincubated with β2GPI at 20 °C. After 1 h macrophage uptake was determined in the presence of the indicated inhibitors (20 mm). To determine whether putative PS recognition pathways are involved in the specific uptake of PS·β2GPI complexes by macrophages, uptake was determined in the presence of antibodies to CD36 (6Rigotti A. Acton S.L Krieger M. J. Biol. Chem. 1995; 270: 16221-16224Abstract Full Text Full Text PDF PubMed Scopus (498) Google Scholar, 7Ren Y. Silverstein R.L. Allen J. Savill J. J. Exp. Med. 1995; 181: 1857-1862Crossref PubMed Scopus (354) Google Scholar, 8Fukasawa M. Adachi H. Hirota K. Tsujimoto M. Arai H. Inoue K. Exp. Cell. Res. 1996; 222: 246-250Crossref PubMed Scopus (139) Google Scholar), CD68 (4Ramprasad M.P. Fischer W. Witztum J.L. Sambrano G.R. Quehenberger O. Steinberg D. Proc. Natl. Acad. Sci. U. S. A. 1995; 92: 9580-9584Crossref PubMed Scopus (299) Google Scholar), and CD14 (2Pradhan D. Krahling S. Williamson P. Schlegel R.A. Mol. Biol. Cell. 1997; 8: 767-778Crossref PubMed Scopus (127) Google Scholar, 9Flora P.K. Gregory C.D. Eur. J. Immunol. 1994; 24: 2625-2632Crossref PubMed Scopus (116) Google Scholar, 11Devitt A. Moffat O.D. Raykundalia C. Capra J.D. Simons D.L. Gregory C.D. Nature. 1998; 392: 505-509Crossref PubMed Scopus (575) Google Scholar). As determined by fluorescence microscopy using fluorescein-conjugated secondary antibodies, all the monoclonals, with the exception of CD36, bound to the macrophage membrane (not shown). Unlike the significant inhibition (∼50%) obtained with apoptotic cells (9Flora P.K. Gregory C.D. Eur. J. Immunol. 1994; 24: 2625-2632Crossref PubMed Scopus (116) Google Scholar, 11Devitt A. Moffat O.D. Raykundalia C. Capra J.D. Simons D.L. Gregory C.D. Nature. 1998; 392: 505-509Crossref PubMed Scopus (575) Google Scholar) and symmetric red blood cell ghosts (2Pradhan D. Krahling S. Williamson P. Schlegel R.A. Mol. Biol. Cell. 1997; 8: 767-778Crossref PubMed Scopus (127) Google Scholar), 61D3 antibodies (anti-CD14) did not significantly inhibit the uptake of PS·β2GPI (Table II). Antibodies against other macrophage surface antigens (CD11b, CD36, and CD68) and against other CD14 epitopes (monoclonals TUK4 and UCHM-1) were also without significant effect. Surprisingly, all of the monoclonals with the exception of 61D3 significantly enhanced the uptake of PS/PC vesicles in the absence of β2GPI. The reasons for this observation are not clear.Table IIEffect of antibodies to macrophage cell surface receptors on PS·β2GPI uptakeAntibody2-aThe antibody concentrations used were: β2GPI F(ab′)2, 80 μg/ml; CD11b, 37 μg/ml; CD36, 100 μg/ml; CD68, 67 μg/ml; CD14 (TUK4), 12.5 μg/ml; CD14 (UCHM-1), 44 μg/ml; CD14 (61D3), 67 μg/ml.125I-lipid uptake2-bResults are expressed as counts/min uptake with percent uptake in parentheses.PS·β2GPIPS aloneNone13136 (100)7352 (100)β2GPI F(ab′)26830 (52)7116 (97)CD11b (clone 44)15583 (119)13315 (181)CD36 (SM0)2-cFluorescent staining failed to detect CD36 antigen on the cell surface.15102 (115)10780 (147)CD68 (KP1)11197 (85)22772 (310)CD14 (TUK4)10581 (80)26287 (357)CD14 (UCHM-1)15044 (114)14704 (200)CD14 (61D3)12099 (92)7387 (100)125I-Labeled PS/PC (1/1) vesicles were preincubated with β2GPI at 20 °C. Macrophage uptake was then determined in the presence of the indicated antibodies.2-a The antibody concentrations used were: β2GPI F(ab′)2, 80 μg/ml; CD11b, 37 μg/ml; CD36, 100 μg/ml; CD68, 67 μg/ml; CD14 (TUK4), 12.5 μg/ml; CD14 (UCHM-1), 44 μg/ml; CD14 (61D3), 67 μg/ml.2-b Results are expressed as counts/min uptake with percent uptake in parentheses.2-c Fluorescent staining failed to detect CD36 antigen on the cell surface. Open table in a new tab 125I-Labeled PS/PC (1/1) vesicles were preincubated with β2GPI at 20 °C. Macrophage uptake was then determined in the presence of the indicated antibodies. β2GPI is a well characterized plasma glycoprotein that binds negatively charged phospholipids. This property is responsible for regulating thrombosis by competing with clotting factors for PS expressed on the surface of activated platelets (19Brighton T.A. Hogg P.J. Dai Y.-P. Murray B.H. Choing B.H. Chesterman C.N. Br. J. Hematol. 1996; 93: 185-194Crossref PubMed Scopus (89) Google Scholar). Similar PS binding activities have also been shown to occur with synthetic negatively charged phospholipid vesicles (15Wurm H.J. Int. J. Biochem. 1984; 16: 511-515Crossref PubMed Scopus (225) Google Scholar, 16Chonn A. Semple S.C. Cullis P.R. J. Biol. Chem. 1995; 270: 25845-25849Abstract Full Text Full Text PDF PubMed Scopus (176) Google Scholar) and apoptotic thymocytes (17Price B.E. Rauch J. Shia M.A. Walsh M.T. Lieberthal W. Gilligan H.M. O'Laughlin T. Koh J.S. Levine J.S. J. Immunol. 1996; 157: 2201-2208PubMed Google Scholar, 18Balasubramanian K. Chandra J. Schroit A.J. J. Biol. Chem. 1997; 272: 31113-31117Abstract Full Text Full Text PDF PubMed Scopus (146) Google Scholar). Formation of these PS·β2GPI complexes is associated with rapid clearance of the PS-expressing particle from the peripheral circulation (16Chonn A. Semple S.C. Cullis P.R. J. Biol. Chem. 1995; 270: 25845-25849Abstract Full Text Full Text PDF PubMed Scopus (176) Google Scholar) and phagocytosis of PS-expressing cells in vitro (18Balasubramanian K. Chandra J. Schroit A.J. J. Biol. Chem. 1997; 272: 31113-31117Abstract Full Text Full Text PDF PubMed Scopus (146) Google Scholar). Interestingly, the binding of β2GPI to PS has been shown to result in a major change in the proteins conformation (29Matsuura E. Igarashi Y. Yasuda T. Triplett D.A. Koike T. J. Exp. Med. 1994; 179: 457-462Crossref PubMed Scopus (566) Google Scholar, 30Borchman D. Harris E.N. Pierangeli S.S. Lamba O.P. Clin. Exp. Immunol. 1995; 102: 373-378Crossref PubMed Scopus (46) Google Scholar) that might result in the expression of a new epitope (31Hagihara Y. Goto Y. Kato H. Yoshimura T. J. Biochem. (Tokyo). 1995; 118: 129-136Crossref PubMed Scopus (47) Google Scholar), which, in certain individuals, generates an autoimmune response. While the mechanism for the generation of these immune responses is not known, this new epitope could be responsible for the recognition and removal of PS-expressing apoptotic and senescent cells from the host. Using an in vitro model for macrophage binding, we showed that the uptake of PS liposomes by macrophages was greatly enhanced by the addition of β2GPI that saturated at ∼2 μm. Since the average concentration of β2GPI in normal human plasma is about 4 μm(13Cohnen G. J. Lab. Clin. Med. 1969; 75: 212-216Google Scholar), these data raise the possibility that this property could be the principal function of β2GPI in vivo. Interestingly, as shown in Fig. 2, ligand-free β2GPI did not bind macrophages. However, once β2GPI bound PS, the complex became rapidly associated with the macrophage membrane. The requirement for ligand binding was further shown by the inability of macrophages to bind diketene-treated (lysine-blocked) β2GPI even in the presence of PS. PS·β2GPI complex binding to macrophages was shown to be inhibited by lysine and arginine as well as negatively charged ions including organic acids and phosphate (Table I). These compounds did not affect β2GPI binding to its ligand since they did not inhibit precipitation of the complex in a gel diffusion assay. This suggests that the binding of the complex to the macrophage membrane requires specific electrostatic interactions that are unlike those involved in the binding of β2GPI to its ligand. Amino acid analysis showed that β2GPI consists of five characteristic sushi domains (32Kato H. Enjyoji K-I. Biochemistry. 1991; 30: 11687-11694Crossref PubMed Scopus (132) Google Scholar) with domain V being principally responsible for the lipid binding properties of the protein (28Hunt J. Krilis S. J. Immunol. 1994; 152: 653-659PubMed Google Scholar). While the lysines present on domain V are known to be critical for lipid binding (28Hunt J. Krilis S. J. Immunol. 1994; 152: 653-659PubMed Google Scholar), the experiments described here cannot exclude the possibility that these or other lysines are also required for ligand-dependent macrophage binding. Acylation of sulfhydryls with NEM, on the other hand, inhibited PS-dependent macrophage binding but not PS binding to β2GPI (Fig. 4). Because human β2GPI might contain a free sulfhydryl (Cys102 and/or Cys169) (33Lozier J. Takahashi N. Putnam F.W. Proc. Natl. Acad. Sci U. S. A. 1984; 81: 3640-3644Crossref PubMed Scopus (320) Google Scholar, 34Steinkasserer A. Estaller C. Weiss E. Sim R.B. Day A.J. Biochem. J. 1991; 277: 387-391Crossref PubMed Scopus (181) Google Scholar), it is possible that acylation of one or both these moieties inhibits the putative conformational change required to promote macrophage binding of the PS·β2GPI complex. This raises the possibility that domains II and/or III, harbor a hidden moiety critical to macrophage binding. Additional support for the involvement of these domains in macrophage binding can be obtained from results which showed that removal of the carbohydrate moieties (33Lozier J. Takahashi N. Putnam F.W. Proc. Natl. Acad. Sci U. S. A. 1984; 81: 3640-3644Crossref PubMed Scopus (320) Google Scholar) resulted in >3-fold enhancement in β2GPI-dependent uptake (Fig. 6). Several studies have suggested that the redistribution of PS from the cells inner to outer leaflet signals for removal of these cells by the reticuloendothelial system (1Fadok V.A. Voelker D.R. Campbell P.A. Cohen J.J. Bratton D.L. Henson P.M. J. Immunol. 1992; 148: 2207-2216Crossref PubMed Google Scholar, 2Pradhan D. Krahling S. Williamson P. Schlegel R.A. Mol. Biol. Cell. 1997; 8: 767-778Crossref PubMed Scopus (127) Google Scholar, 3Zwaal R.F.A. Schroit A.J. Blood. 1997; 89: 1121-1132Crossref PubMed Google Scholar, 16Chonn A. Semple S.C. Cullis P.R. J. Biol. Chem. 1995; 270: 25845-25849Abstract Full Text Full Text PDF PubMed Scopus (176) Google Scholar). Although several mechanisms might be responsible for phagocyte recognition of PS expressing apoptotic cells, Price et al. (17Price B.E. Rauch J. Shia M.A. Walsh M.T. Lieberthal W. Gilligan H.M. O'Laughlin T. Koh J.S. Levine J.S. J. Immunol. 1996; 157: 2201-2208PubMed Google Scholar) proposed that the interaction of circulating β2GPI with redistributed anionic phospholipid may, by itself, generate a novel ligand by which apoptotic cells are recognized. Indeed, other studies have indicated that β2GPI could play a central role in this recognition process (16Chonn A. Semple S.C. Cullis P.R. J. Biol. Chem. 1995; 270: 25845-25849Abstract Full Text Full Text PDF PubMed Scopus (176) Google Scholar). Combined with these previous studies, the data presented here provide evidence for the existence of a receptor on the macrophage membrane that specifically binds β2GPI in a ligand-dependent manner. Although the motif on the protein responsible for the macrophage membrane interaction is not known, it could result from a lipid-dependent conformational change (29Matsuura E. Igarashi Y. Yasuda T. Triplett D.A. Koike T. J. Exp. Med. 1994; 179: 457-462Crossref PubMed Scopus (566) Google Scholar, 30Borchman D. Harris E.N. Pierangeli S.S. Lamba O.P. Clin. Exp. Immunol. 1995; 102: 373-378Crossref PubMed Scopus (46) Google Scholar) that is specifically bound to a cell surface receptor, a process that can be inhibited with anti-β2GPI F(ab′)2 (Fig. 5). Several reports have suggested the involvement of macrosialin (CD68) (4Ramprasad M.P. Fischer W. Witztum J.L. Sambrano G.R. Quehenberger O. Steinberg D. Proc. Natl. Acad. Sci. U. S. A. 1995; 92: 9580-9584Crossref PubMed Scopus (299) Google Scholar), scavenger receptor (CD36) (6Rigotti A. Acton S.L Krieger M. J. Biol. Chem. 1995; 270: 16221-16224Abstract Full Text Full Text PDF PubMed Scopus (498) Google Scholar, 7Ren Y. Silverstein R.L. Allen J. Savill J. J. Exp. Med. 1995; 181: 1857-1862Crossref PubMed Scopus (354) Google Scholar, 8Fukasawa M. Adachi H. Hirota K. Tsujimoto M. Arai H. Inoue K. Exp. Cell. Res. 1996; 222: 246-250Crossref PubMed Scopus (139) Google Scholar), and the lipopolysaccharide receptor (CD14) (2Pradhan D. Krahling S. Williamson P. Schlegel R.A. Mol. Biol. Cell. 1997; 8: 767-778Crossref PubMed Scopus (127) Google Scholar, 9Flora P.K. Gregory C.D. Eur. J. Immunol. 1994; 24: 2625-2632Crossref PubMed Scopus (116) Google Scholar, 11Devitt A. Moffat O.D. Raykundalia C. Capra J.D. Simons D.L. Gregory C.D. Nature. 1998; 392: 505-509Crossref PubMed Scopus (575) Google Scholar) in the recognition of PS on apoptotic cells. Antibodies directed against these cell surface moieties, however, did not significantly inhibit β2GPI-dependent PS uptake. The inability to obtain more than 20% inhibition raises the possibility that either more than one cell surface component is involved in β2GPI-dependent recognition or that recognition is inhibited because of steric hindrance by antibody bound to an unrelated proximal site. Although further studies will be required to identify the putative PS·β2GPI-dependent macrophage receptor, the data presented here argue for the existence of such a receptor. Because of the relative abundance of β2GPI in plasma, it could play an important physiologic role by bridging PS-expressing cells to phagocytes for their ultimate disposal. We thank Drs. Killion and Cookie for constructive criticism and Anh Lee for technical assistance.